Technological Innovations in Cocoa Cultivation for Enhancing Productivity and Bean Quality - Imran Imran (Journal of Agriculture, Agribusiness, Welfare, Technology, Humanity, Environment, Social, and Economy, 2025)
Technological innovation in cocoa cultivation has become increasingly urgent in line with the growing global demand for high-quality cocoa products. This literature review aims to evaluate various modern agricultural technologies applied in cocoa cultivation and examine how these technologies contribute to improving yield and bean quality. The review covers innovations such as precision irrigation systems, sensor-based fertilization, the use of high-yield and disease-resistant varieties, agroforestry practices, and post-harvest technologies including controlled fermentation and mechanical drying. The methodology involved a systematic search of scientific articles, technical reports, and publications from agricultural institutions published between 2010 and 2025, using databases such as Scopus, Google Scholar, and the portals of IPB University and the Indonesian Agency for Agricultural Research and Development. Selection criteria were based on relevance, empirical impact, and methodological rigor. The findings identified five key domains of innovation: irrigation and water management, soil fertility and nutrient management, genetic improvement of varieties, agroforestry systems, and post-harvest technologies. Each innovation demonstrated significant improvements in yield (ranging from 20–50%) and bean quality (sensory attributes, fat content, product cleanliness). The integration of multiple technologies produced higher synergistic effects. Key challenges include slow adoption due to limited capital and farmers’ technical knowledge, as well as inadequate infrastructure. Recommendations include enhancing access to technology training, providing policy and financial support, and conducting further research on the application of digital and IoT-based technologies in cocoa cultivation. This study provides a foundation for understanding and developing sustainable cocoa cultivation strategies in the modern era.